PENGARUH WORK-LIFE BALANCE DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN: (Studi Pada Karyawan Grand Inna Medan) - Nadapdap, Brian Fransisco; Harahap, Kartini (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
Employee performance is a crucial factor in determining a company's success. It reflects the contributions and achievements of individual employees in their roles. This study investigates the impact of Work-Life Balance and the work environment on the performance of Grand Inna Medan employees, both individually and collectively. Employing a quantitative approach, the research collected data from 50 respondents through a Likert scale questionnaire and analyzed it using multiple linear regression in SPSS. The findings reveal that Work-Life Balance and the work environment each have a partial impact on employee performance, supported by their respective t-values. Moreover, the simultaneous analysis demonstrates that these variables collectively exert a significant influence on employee performance, as indicated by an F-value surpassing the critical threshold. The research's 18.1% Adjusted R Square suggests that 81.9% of the variation in employee performance is attributed to unexplored factors beyond the scope of this study. These findings highlight the importance of Work-Life Balance and the work environment in enhancing employee performance and ultimately contributing to the success of Grand Inna Medan and similar organizations.